How successful people think change your thinking, change your life - Maxwell, John C., 1947- (New York : Hachette Audio, 2011)
The author shares the eleven secrets that highly successful people use to succeed in life and work, including seeing beyond one's own needs, removing mental distractions, working with others, and examining the past for a better understanding of the future.
Unabridged.
Keywords: Success -- Psychological aspects; Thought and thinking; Success -- Psychological aspects; Thought and thinking